Serotonin System Implication in l-DOPA-Induced Dyskinesia: From Animal Models to Clinical Investigations - Carta, Manolo; Tronci, Elisabetta (Frontiers in Neurology, 2014)
In the recent years the serotonin system has emerged as a key player in the induction of L-DOPA-induced dyskinesia in animal models of Parkinson’s disease. In fact, serotonin neurons possess the enzymatic machinery able to convert exogenous L-DOPA to dopamine, and mediate its vesicular storage and release. However, serotonin neurons lack a feedback control mechanism able to regulate synaptic dopamine levels. While in a situation of partial dopamine depletion spared dopamine terminals can buffer dopamine released from serotonin neurons, the progression of dopamine neuron degeneration impairs this protective mechanism, causing swings in synaptic dopamine levels and pulsatile stimulation of post-synaptic dopamine receptors. In line with this view, removal of serotonin neurons by selective toxin, or pharmacological silencing of their activity, produced complete suppression of L-DOPA-induced dyskinesia in animal models of Parkinson’s disease. In this article we will revise the experimental evidence pointing to the important role of serotonin neurons in dyskinesia, and we will discuss the clinical implications.